IDENTIFIKASI DAN PROFIL RESISTENSI BAKTERI PADA MINUMAN AIR TAHU DAN AIR TEBU DI WILAYAH KOTA PONTIANAK - Aditia, Aditia; Nuswantoro, Ari; Djohan, Herlinda; Ihsan, Bagus Muhammad; Uq'ma, Nurul; Shafitri, Anisya Nur; Affifatuzahara, Affifatuzahara; Al-qorifah, Fahma Ajeng; Anjelica, Benedikta (LPPM Institut Pendidikan Nusantara Global, 2023)
Tofu and sugarcane juice drinks are in great demand because they taste delicious and affordable. These drinks can be contaminated with pathogenic bacteria due to hygiene and poor environment. Contamination of pathogenic bacteria that are resistant to antibiotics is a serious health threat. The objective of this study is to identify and provide antibiotic resistance bacteria from tofu and sugarcane juice drinks overview. This Study is a descriptive-observation with a cross-sectional design. Bacterial identification is carried out by culture, while resistance testing is carried out by Kirby-Bauer. Penicillin, amoxicillin, ampicillin, ciprofloxacin, chloramphenicol, gentamicin, tetracycline, and vancomycin were used. 43 samples of tofu water drink and 70 samples of sugarcane juice drink were selected by purposive sampling. Staphylococcus aureus, Salmonella typhi, Enterobacter aerogenes, and Klebsiella pneumoniae founds in tofu drinks, while Enterobacter aerogenes, Salmonella typhi, Shigella dysenteriae, and Escherichia coli founds in sugarcane juice. Staphylococcus aureus resistant to penicillin (100%), Salmonella typhi resistant to penicillin (66.6%), Enterobacter aerogenes resistant to tetracycline (70%), Klebsiella pneumoniae resistant to penicillin (100%), Shigella dysenteriae resistant to ampicillin and gentamicin (100%), and Escherichia coli resistant to vancomycin (100%). Pathogenic-resistant bacteria in tofu and sugarcane juice drinks show the risk of spreading resistant bacteria which can trigger bacterial resistance with a wider spectrum.